ISO 14001:2015 and ISO 9001:2015 Implementation in Con-struction Company: Study Case: PT. Adhi Karya (Persero) Tbk, PT. Nusa Kon-struksi Enjiniring Tbk, Eiffage, and Acciona, S,A - Rizka Dwi Apriliani; Yemima Marnalita Hasibuan; Filson Maratur Sidjabat (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Banten Jaya, 2019)
In this era of globalization, competition between producers is commonplace as well as companies in the construction sector that have developed a lot. This causes the quality of the products and services to be increasingly considered. Thus, construction company needs to get standardized recognition up to international standards stating that the products and systems used are worth buying. The international standard that is often used by various companies is ISO 14001: 2015, which states a commitment to save the environment, and ISO 9001: 2015 which states a commitment to increase customer satisfaction. The aim of this study is to know the implementation and achievement of these standards in construction companies. This study discusses implementation in 4 domestic and foreign companies as representative namely, PT. Adhi Karya (persero) Tbk, PT. Nusa Konstruksi Enjinirin, Tbk, Eiffage, and Acciona, S, A. The method used in this study is a qualitative research method based on the annual report of each company. The results of this study known that each company has its own strategy to achieve ISO 14001: 2015, in PT. Nusa Konstruksi Enjiniring Tbk (NKE) they do direct action in protecting the environment such as managing the waste produced, preventing pollution, also following the existing regulation. In PT. Adhi Karya, they more consider about the health and safety of the work place, prioritizing the use of eco-friendly and energy saving products, pollution prevention and natural resources. Acciona, S,A and Eiffage they more consider about the environmental protection norms it is common to build designated infrastructure to preserve the environment and treat the waste.